Assessment of Schistosoma mansoni and soil-transmitted helminth infections and the diagnostic performance of the circulating cathodic antigen test among schoolchildren in Tulla district, Sidama region, Southern Ethiopia - Fitsum Getachew; Demissie Assegu; Biniyam Kijineh; Bamlaku Tadege (PLoS ONE, 2025)
Background STH and S. mansoni pose significant public health challenges in regions with inadequate sanitation. Existing research on S. mansoni intensity remains limited in the study area. S. mansoni diagnosis traditionally relies on the KK method, though the POC-CCA urine test offers a rapid alternative with high sensitivity. This study aimed to assess the prevalence and risk factors of S. mansoni and STH infections. It also evaluated the intensity of S. mansoni and compared the performance of the POC-CCA test to that of KK. Methods A cross-sectional study was conducted among schoolchildren in the Tulla district, Sidama region, from April to June 2024, using a purposive sampling approach. Data were collected through pre-structured questionnaires, and stool samples were analyzed using the KK method, while urine samples were analyzed with the POC-CCA technique. A logistic regression model was employed to examine potential associations between infections and risk factors, the Kappa statistic assessed agreement between tests, and the McNemar chi-square test compared the sensitivity and specificity of the diagnostic methods. Result The prevalence of S. mansoni with two combined tests was 36.5% (20.1% by KK and 34.4% by POC-CCA). Activities like irrigation, swimming, and bathing showed significant associations with S. mansoni infection. The prevalence of STH was 48.8%, with A. lumbricoides (34%) as the most common, followed by T. trichuria (8.2%), hookworm (5.7%), Taenia species (1.3%), H . nana (0.6%), and E.vermicularis (0.2%). Factors like hand washing, fingernail trimming, lack of latrines, and educational status were significantly linked to STH infections. The POC-CCA test demonstrated higher sensitivity (89.6%) than the KK technique (McNemar test χ²m = 52.3, p < 0.001). Conclusions The moderate prevalence of S. mansoni and STH infections, coupled with socio-demographic factors, behaviours, hygiene practices, and sanitation issues associated with these infections, highlights the need for additional control measures beyond deworming. Implementing a highly sensitive POC- CCA test alongside the KK method in low-endemic areas could improve diagnostic accuracy and enhance disease management outcomes.